Evaluation of high-quality dolomite aggregate for asphalt wearing course - Vorobjovas, Viktoras; Šernas, Ovidijus; Žilionienė, Daiva; Šneideraitienė, Lina; Filotenkovas, Vilius (International Conference “Environmental Engineering”, 2017)
In Lithuania dolomite is the third most excavated by the amount mineral resource, which is mostly used in subbase layer and hot asphalt mixtures for asphalt binder and base courses. Although, for asphalt wearing layer are often used granite aggregates, but this magmatic rock is imported from foreign countries. In one of the quarries of JSC “Dolomitas” higher quality dolomite is produced, which has similar mechanical properties to granite. To determine changes in mechanical properties of the different type of aggregates while using in the road, high-quality dolomite and two types of granite were chosen for laboratory testing. In this study, for evaluation of physical and mechanical properties of aggregates by laboratory tests for determining resistance to freezing hawing, resistance to fragmentation, and polished stone value were carried out. Also, according to the results of laboratory testing, high-quality dolomite aggregate showed equal performance comparing to granite aggregates.